Gen Y and Gen Z Communication Style - Humaira, Raslie; Ting, Su Hie (Universidad de Almería, 2021)
Communication style plays a crucial role in managing the multigenerational ecosystem of the present world. This study examined the communication style of Gen Y and Gen Z. The participants were 311 youth (Gen Y, 68; Gen Z, 243). The questionnaire on communication style was developed based on Hartman and McCambridge (2011). The online survey was conducted from 6 April 2020 to 11 May 2020 by distributing the questionnaire link to people who were in the Gen Y and Gen Z age groups. The results showed that both groups were similar in their general characteristics, which included preferences for group-work, affirmation, clear rules, and for their opinions to be valued. They liked face-to-face communication, and using visuals for online communication. There were significant differences in some of their study and work habits, that is, the Gen Y are better than Gen Z at analysing information obtained from the Internet, and handling a lot of work at one time, whereas Gen Z expected more instantaneous feedback than Gen Y. As for communication style, they were amiable communicators who were low on assertiveness, prioritised relationship over task in task completion, and had a slow-paced communication style. The results showed that Gen Y and Gen Z had some style-typing ability, whereby they compared their communication style with their peers. More practised style-flexing, as in fitting their communication to the target group but Gen Y had a stronger information-focus. Their demographic background (gender, ethnic group, socio-economic status) did not influence their communication style, indicating the stronger influence of their generational cohort. The study suggests that employers who require goal-oriented communication need to make their expectations clear to Gen Y and Gen Z employees.